Quantifying the Fiscal Effects of Trade Reform - Devarajan, Shantayanan, 1954- 1954- (The World Bank, 1999)
August 1999 - A general equilibrium tax model estimated for 60 countries provides a simple but rigorous method for estimating the fiscal impact of trade reform. Using a tax model of an open economy, Devarajan, Go, and Li provide a simple but rigorous method for estimating the fiscal impact of trade reform. Both the direction and the magnitude of the fiscal consequences of trade reform depend on the elasticities of substitution and transformation between foreign and domestic goods, so they provide empirical estimates of those elasticities. They also discuss the implications of their analysis for public revenue. In general, they find that it matters what the values of the two elasticities are relative to each other. If only one of the elasticities is low (close to zero), revenue will drop unequivocally as a result of tariff reform, reaching close to the maximum drop whether or not the other elasticity is high. For imports to grow and tariff collection to compensate for the tax cut, the import elasticity has to be high. Because of the balance of trade constraint, however, imports cannot substitute for domestic goods unless supply is able to switch toward exports. Hence, the export transformation elasticity has to be high as well. As substitution possibilities between foreign and domestic goods increase, a tariff reform can theoretically be self-financing. But if the elasticities are less than large, tax revenue will fall with tariff reduction and further fiscal adjustments will be necessary. Devarajan, Go, and Li provide empirical estimates of the possible range of values for the elasticities of about 60 countries, using various approaches. The elasticities range from 0 to only 3 in most cases - nowhere near the point at which tariff reform can be self-financing.